Meningkatkan Loyalitas Pelanggan Melalui Restaurant Atmosphere, Kualitas Pelayanan, dan Product Quality: Studi Pengaruh Terhadap Repurchase Intention pada Avera Bali Restaurant di Legian - Dewi, Putu Dian Prasetia; Maheswari, Anak Agung Istri Agung; Parasari, Nyoman Sri Manik (Masyarakat Ekonomi Syariah Bogor, 2025)
Bali’s tourism sector continues to strengthen, supported by its positive image and the steady increase in both domestic and international visitor arrivals. Most tourists come to Bali not only to enjoy its well-known attractions but also to seek a complete experience ranging from the ambiance and service to the overall impression they receive after dining. Avera Bali, a restaurant located in Legian, has experienced fluctuating customer visits from January to July 2025. This instability is suspected to be related to varying Google Review comments, including critiques about long waiting times for food, overly loud music, and insufficient service quality. This study aims to determine whether restaurant atmosphere, service quality, and product quality influence repurchase intention. A quantitative approach was used by distributing questionnaires to 144 respondents who met specific criteria. The research instruments included descriptive statistics, validity tests, and reliability tests, followed by classical assumption testing and multiple linear regression analysis. The findings show that restaurant atmosphere, service quality, and product quality each have a positive and significant effect on repurchase intention. Future research is advised to enhance the overall dining environment, provide regular staff training, maintain product consistency, and incorporate additional variables that may influence repurchase intention, as well as examine different objects to broaden and compare the results.